Władza sądownicza biskupa galijskiego według Grzegorza z Tours - Piotr Nowak (Vox Patrum, 2014)
From the examples preserved in literature of Gregory of Tours the Gallic Church in the 6th century accomplished a crucial role in the judiciary system of the age. Bishops used to resolve not only own matters concerning the clergy or Canon Laws but also used to pass judgements on various arguments in which lay people were the parties. The highest hierarch acted alone or in the presence of the lay judge and other participants of the dispute and was unquestionably fulfilling formal procedural line. In the judicial procedure the bishop was appearing mainly as a mediator, with hope to reach the compromise by using his own high prestige and following the current law. In this procedure he was guided by a principle of the Christian mercy, clearly considering the Church learning in settling matters according the God’s justice, for which to its own conviction, he was a representative. Gregory’s of Tours iustitia implied such ideas, like the faithful life, charitable activity and the fair revenge. Bishops of this period were appearing consciously in the role of God’s messengers spreading the peace and love, and having the duty to support and protect the poor. In this way bishops are using judicial activity as the form of the pastoral ministry. Through such an attitude they were undoubtedly contributing to create a new civilization and relief the barbaric customs of Dark Ages epoch.